The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1039/c2bm00114d
|View full text |Cite
|
Sign up to set email alerts
|

Bio-ink for on-demand printing of living cells

Abstract: Drop-on-demand bioprinting allows the controlled placement of living cells, and will benefit research in the fields of tissue engineering, drug screening and toxicology. We show that a bio-ink based on a novel microgel suspension in a surfactant-containing tissue culture medium can be used to reproducibly print several different cell types, from two different commercially available drop-on-demand printing systems, over long printing periods. The bio-ink maintains a stable cell suspension, preventing the settli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(144 citation statements)
references
References 38 publications
2
140
0
2
Order By: Relevance
“…Chahal et al successfully addressed this issue by using a surfactant (Ficoll-PM 400) to control the ink density resulting in reliable cell printing through a commercial single nozzle (MicroFab, Germany) over 90 min (Chahal et al 2012). Ferris et al showed that a bio-ink based on a novel microgel suspension in surfactant-containing tissue culture media could be used to prevent cell settling and aggregation (Ferris et al 2013). The stable suspension and optimal fluid properties of the bio-ink allowed reproducible printing of several different cell types, from two different commercially available drop-on-demand printing systems, over long printing periods.…”
Section: Parsa Et Al Used Single Piezoelectric Nozzle Ejectors (60-1mentioning
confidence: 99%
See 2 more Smart Citations
“…Chahal et al successfully addressed this issue by using a surfactant (Ficoll-PM 400) to control the ink density resulting in reliable cell printing through a commercial single nozzle (MicroFab, Germany) over 90 min (Chahal et al 2012). Ferris et al showed that a bio-ink based on a novel microgel suspension in surfactant-containing tissue culture media could be used to prevent cell settling and aggregation (Ferris et al 2013). The stable suspension and optimal fluid properties of the bio-ink allowed reproducible printing of several different cell types, from two different commercially available drop-on-demand printing systems, over long printing periods.…”
Section: Parsa Et Al Used Single Piezoelectric Nozzle Ejectors (60-1mentioning
confidence: 99%
“…The issue of settling and aggregation of cells has recently been successfully addressed (Chahal et al 2012;Ferris et al 2013). Furthermore, work to date has utilised thermal inkjet , single-nozzle piezoelectric, and multiple nozzle piezoelectric printheads (Ferris et al 2013).…”
Section: Comparison Of Approaches and Remaining Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…pigmented inks), also generate another set of constraints (particle size, morphology and concentration) which are normally empirically evaluated for a given ink and print head combination. While a large number of different materials have been successfully printed by inkjet, including cells, colloids and nanomaterials (Ferris et al 2013, Perelaer et al 2006, van Deen et al 2013, ensuring that a material will print reliably and consistently in an industrial context is much more challenging and requires careful and long-term testing of the proposed system in conjunction with continued quality control.…”
Section: Section 1 Introduction To Inkjet Printing Technologiesmentioning
confidence: 99%
“…In the work by Ferris et al shown in Fig. 7a, neural (PC-12) and skeletal muscle (C2C12) cells were encapsulated within the low-acyl gellan gum by a droplet-based bioprinting technique [107]. After 8 days of culture, the construct exhibited the extension of dense neural networks from PC12 cells into surrounding areas populated by skeletal muscle cells.…”
Section: Bioprinting Of Neural Tissuesmentioning
confidence: 99%